Temples of the Kama Sutra - Discovery Channel (Firm).; Archeological Institute of America (Bethesda, Md. Discovery Communications, 1995)
Temple of the Kama Sutra relates the erotic sculptures of the 10th-12th century Hindu temples at Khajuraho to the 4th century sex manual, Kamasutra.
Distributed in the Philippines by Magnavision Home Video.
Originally shown on the television program Archaeology.
Producers, Tom Naughton, Nicolas Valcour ; director, Joseph Wiecha ; writer, Robin Bates.
Host, John Rhys-Davies.
Keywords: Temples, Hindu -- India; Erotic sculpture, Indic -- India -- Khajuraho; Sex -- Religious aspects -- India -- Khajuraho; Khajuraho (India) -- Buildings, structures, etc